Hollow Au nanoflower substrates for identification and discrimination of the differentiation of bone marrow mesenchymal stem cells by surface-enhanced Raman spectroscopy. Issue 30 (17th July 2017) - Cao, Xiaowei; Shan, Yibo; Tan, Lianqiao; Yu, Xi; Bao, Min; Li, Wei; Shi, Hongcan
Abstract : In this work, a novel surface-enhanced Raman scattering (SERS) substrates based on hollow gold nanoflower (HAuNF)-decorated silicon wafers have been fabricated for detection and identification of the differentiation of bone marrow mesenchymal stem cells. Abstract : Bone marrow mesenchymal stem cells (BMSCs) are multipotent stem cells, which play an important role in the repair of bone injury, angiogenesis, immune diseases, cancer invasion and metastasis. Therefore, increasing attention has been focused on the study of BMSCs. However, the identification and discrimination of the undifferentiated and differentiated BMSCs, which are closely related and morphologically similar, are still a challenge using traditional methods. In this study, we report a novel surface-enhanced Raman scattering (SERS) substrate based on hollow gold nanoflower (HAuNF)-decorated silicon wafers for distinguishing the differentiation of BMSCs. The flower-like, hollow Au nanoparticles were successfully synthesized by a seed-mediated growth approach. We demonstrated that fabricated HAuNF substrates had very good reproducibility, homogeneous SERS activity and a high SERS effect. Using HAuNF substrates as a high-performance in vitro sensing platform allowed us to monitor the changes in the cellular biochemical composition during the differentiation of BMSCs. SERS spectra were analyzed using principal component analysis (PCA), which successfully segregated the subtypes of BMSCs. Furthermore, the results of biological assay suggested that the adipogenic inductor and the osteogenic inductor could induce the differentiation of BMSCs into adipocytes and osteocytes, respectively. The SERS technique based on HAuNF substrates provides a sensitive, efficient and non-invasive detection method for studying the differentiation of stem cells.